The Formation of Human Qualities for Life in Teachers: A Review of Scientific Literature - Vásquez, Mgs. Rosa Ildaura Troya; Peña, Dr. Edilberto Calle; Troya, Lcdo. Yarov Javier Cabezas (Journal of Ecohumanism, 2024)
The purpose of this article is to analyze the literature of the last five years to provide a perspective on the development of qualities for life in teachers. The research design is a literature review with a qualitative approach in which the systematic literature review technique was used in Scopus, Scielo, Redalyc, Dialnet, Proquest, Erih Plus, DOAJ (Directory of Open Access Journals), Latindex, the library and the Universidad César Vallejo. The systematic literature review was based on the PRISMA methodology, with inclusion criteria for selection: publications based on a scientific methodology, by a single author or by several authors, published from 2019 to 2023 and as keywords: human qualities for life, human skills, competencies and/or skills. The exclusion criteria ruled out publications from before 2019, without reliable or significant results for this research, which are duplicates and/or have an inconsequential abstract. It was possible to identify in the last five years 17 scientific publications on the development of qualities for life in teachers: six have been published by a single author and 11 collectively, three correspond to 2019, four to 2020, six to 2021 and four to 2022. It was concluded that the issue of the development of qualities for life in teachers is a social and educational phenomenon widely spread worldwide that has generated the interest of several researchers in the last five years.